INTEGRASI DATA SAMPAH SEBAGAI UPAYA MEWUJUDKAN ZERO WASTE MANAGEMENT: STUDI KASUS DI KOTA BANDUNG - Nabilla Salma Khairunisa; Diana Rizky Safitri (Jurnal Analisa Sosiologi, 2020)
This research aims to determine the percentage of the amount of waste in Indonesia by focusing on solving the problem of waste in the city of Bandung. This reason is because the city of Bandung is the background for the occurrence of the National Waste Day every February 21st. This research uses panel data with random-effect methods and quantitative data analysis. The data used are secondary data and primary data. Secondary data was obtained from the website of the Indonesian Bureau of Central Statistics (BPS) and the Ministry of Environment and Forestry with provincial data for 2015-2016 and primary data obtained from direct interviews with the Head of the Bank Sampah Induk Resik Bandung and Bank Sampah Hijau Lestari. Secondary data used in this research uses the percentage of total waste as the dependent variable, population variable, diarrhea, gross regional domestic product, number of technology users, human development index, and number of industries as independent variables. The results of the research using panel data and random-effect methods show that increasing the number of population increases the percentage of the amount of waste in Indonesia, also the increase in technology users, which can reduce the percentage of the amount of waste in Indonesia. This research is important to read to solve the waste problem in Indonesia. Keywords: Bandung, Data integration, Innovation, Regulation, implementation, Trash AbstrakPenelitian ini bertujuan untuk mengetahui persentase jumlah sampah di Indonesia dengan memfokuskan kepada penyelesaian permasalahan sampah di Kota Bandung. Hal ini dikarenakan Kota Bandung merupakan daerah yang melatarbelakangi terjadinya hari sampah nasional pada setiap tanggal 21 Februari. Penelitian ini menggunakan data panel dengan metode random-effect dan  analisis kuantitatif. Data yang digunakan adalah data sekunder dan data primer. Data sekunder didapatkan dari situs Badan Pusat Statistik (BPS) dan Kementerian Lingkungan Hidup dan Kehutanan dengan data provinsi tahun 2015 – 2016 dan data primer didapatkan dari wawancara langsung terhadap Kepala Bank Sampah Induk Kota Bandung dan Bank Sampah Hijau Lestari. Data sekunder yang digunakan dalam penelitian ini menggunakan variabel persentase jumlah sampah sebagai variabel dependen, variabel populasi, diare, gross regional domestic product, jumlah pengguna teknologi, indeks pembangunan manusia, dan jumlah industri sebagai variabel independen. Hasil regresi se dengan menggunakan data panel dan metode random-effect menunjukan bahwa peningkatan jumlah populasi meningkatkan persentase jumlah sampah di Indonesia, serta peningkatan pengguna teknologi dapat menurunkan persentase jumlah sampah di Indonesia. Penelitian ini penting dibaca sebagai upaya untuk menyelesaikan permasalahan sampah di Indonesia. Kata kunci: Bandung, Sampah, Implementasi Undang-Undang, Inovasi, Integrasi Data.